Carbon dioxide insufflation during colonoscopy in inflammatory bowel disease patients: a double-blind, randomized, single-center trial - Falt, Přemysl; Šmajstrla, Vít; Fojtík, Petr; Hill, Martin; Urban, Ondřej (European journal of gastroenterology & hepatology, 2017)
OBJECTIVE: Bowel distension by insufflated air causes abdominal discomfort after colonoscopy. Carbon dioxide (CO2) instead of air insufflation during colonoscopy can reduce postprocedural discomfort in diagnostic and screening cases. Discomfort after colonoscopy and CO2 insufflation have never been studied in inflammatory bowel disease (IBD) patients, characterized by younger age, structural changes of the colon, and need for repeated and frequently uncomfortable colonoscopies. Our trial was designed to evaluate postprocedural discomfort associated with CO2 compared with air insufflation in unsedated or minimally sedated patients with known IBD. METHODS: In a double-blind, randomized, single-center study, 64 patients were randomized to either CO2 insufflation (CO2) or air insufflation colonoscopy (Air). Abdominal pain, bloating, and flatulence scores during 24 h after colonoscopy were recorded using a continuous scale of 0-10 (0=none, 10=maximum discomfort). The primary endpoint used for power calculation was bloating score at 1 h after colonoscopy. RESULTS: Pain, bloating, and flatulence scores at end, 1, and 3 h after colonoscopy were significantly lower in CO2 than in Air arm (P<0.001). Scores at 6, 12, and 24 h were comparable. Procedural parameters such as cecal and terminal ileum intubation rate, intubation and total time, pain during insertion, need for repositioning, and abdominal compression were not different between arms. No complications were recorded in the study. CONCLUSION: Compared with air, CO2 insufflation significantly reduces abdominal pain, bloating, and flatulence scores during at least 3 h after colonoscopy in IBD patients, achieving comparable intraprocedural outcomes.
Keywords: dospělí; insuflace; kolon; Abdominal Pain; hypnotika a sedativa; Female; Hypnotics and Sedatives; Adult; ženské pohlaví; Predictive Value of Tests; prediktivní hodnota testů; časové faktory; Colon; Time Factors; lidé; dvojitá slepá metoda; Insufflation; Carbon Dioxide; Colitis, Ulcerative; Colonoscopy; Crohn Disease; Double-Blind Method; bolesti břicha; Male; Czech Republic; Flatulence; ulcerózní kolitida; oxid uhličitý; flatulence; kolonoskopie; Česká republika; lidé středního věku; Crohnova nemoc; mužské pohlaví; Middle Aged; Humans